2006
DOI: 10.1016/j.jtcvs.2005.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of nonelective coronary revascularization with and without cardiopulmonary bypass

Abstract: Nonelective coronary revascularization without cardiopulmonary bypass is associated with comparable operative mortality and stroke and abbreviated length of stay. Off-pump coronary artery bypass might also decrease the need for intra-aortic balloon pump placement and lower the rate of postoperative renal failure and hemorrhage-related re-exploration compared with that of conventional on-pump coronary artery bypass in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…W retrospektywnym wieloośrodkowym badaniu obejmującym 6260 pacjentów (nie podano, jaki był odsetek chorych z NSTE-ACS) poddawanych pilnemu lub nagłemu CABG obserwowana śmiertelność okołooperacyjna wynosiła 3,2% [376]. W jednoośrodkowym badaniu metodą propensity-matched porównano pacjentów poddawanych pilnemu CABG z powodu NSTE--ACS z poddawanymi elektywnemu CABG w stabilnej CAD (n = 342 dla każdej z grup).…”
Section: Krwawienie Niezwiązane Z Dostępem Naczyniowymunclassified
“…W retrospektywnym wieloośrodkowym badaniu obejmującym 6260 pacjentów (nie podano, jaki był odsetek chorych z NSTE-ACS) poddawanych pilnemu lub nagłemu CABG obserwowana śmiertelność okołooperacyjna wynosiła 3,2% [376]. W jednoośrodkowym badaniu metodą propensity-matched porównano pacjentów poddawanych pilnemu CABG z powodu NSTE--ACS z poddawanymi elektywnemu CABG w stabilnej CAD (n = 342 dla każdej z grup).…”
Section: Krwawienie Niezwiązane Z Dostępem Naczyniowymunclassified
“…(Level of Evidence: B) 2. Emergency CABG is recommended after failed PCI for hemodynamic compromise in patients without impairment of the coagulation system and without a previous sternotomy (280,282,283 With widespread stent use as well as effective antiplatelet and antithrombotic therapies, emergency CABG after failed PCI is not commonly performed. In a 2009 analysis of data from almost 22,000 patients undergoing PCI at a single center, only 90 (0.4%) required CABG within 24 hours of PCI (281).…”
Section: Class Imentioning
confidence: 99%
“…Several variables have been shown to be associated with increased perioperative morbidity and mortality rates, including 1) depressed LV systolic function (290), 2) recent ACS (290,291), 3) multivessel CAD and complex lesion morphology (291,292), 4) cardiogenic shock (281), 5) advanced patient age (293), 6) absence of angiographic collaterals (293), 7) previous PCI (294), and 8) a prolonged time delay in transfer to the operating room (293). In patients undergoing emergency CABG for failed PCI, an off-pump procedure may be associated with a reduced incidence of renal failure, need for intra-aortic balloon use, and reoperation for bleeding (283,295).…”
Section: Class Imentioning
confidence: 99%
“…When the surgical treatment occurs urgently and emergently, as Stamou et al [14] demonstrated, it presents greater morbidity and mortality, regardless of the use or not of CPB. They described also that in the off-pump group there is less hospital stay, less incidence of renal failure, less need of intra-aortic balloon and reoperation due to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital stay has proved to be lesser when offpump surgeries are performed [14,22,24]. In the elderly patients, there is reference of 14 days in the on-pump group and 9 days in the off-pump group [15].…”
Section: Discussionmentioning
confidence: 99%